Ulinastatin Inhibits Osteoclastogenesis and Suppresses Ovariectomy-Induced Bone Loss by Downregulating uPAR - Huang, Jun-ming; Ren, Ran-yue; Bao, Yuan; Guo, Jia-chao; Xiang, Wei; Jing, Xing-zhi; Shi, Jia; Zhang, Guo-xiang; Li, Long; Tian, Yong; Kang, Hao; Guo, Feng-jin (Frontiers in Pharmacology, 2018)
Recent studies indicate that uPAR acts a crucial part in cell migration and the modulation of bone homeostasis. As a natural serine protease inhibitor, ulinastatin owns the capacity to reduce proinflammatory factors, downregulate the activation of NF-κB and mitogen-activated protein kinases (MAPKs) signaling pathways. Osteoclastogenesis has been demonstrated to be related with low-grade inflammation which involves cell migration, thus we speculate that ulinastatin may have a certain kind of impact on uPAR so as to be a potential inhibiting agent of osteoclastogenesis. In this research, we investigated the role which ulinastatin plays in RANKL-induced osteoclastogenesis both in vivo and in vitro. Ulinastatin inhibited osteoclast formation and bone resorption in a dose-dependent manner in primary bone marrow-derived macrophages (BMMs), and knockdown of uPAR could completely repress the formation of osteoclasts. At the molecular level, ulinastatin suppressed RANKL-induced activation of cathepsin K, TRAP, nuclear factor-κB (NF-κB) and MAPKs, and decreased the expression of uPAR. At the meantime, ulinastatin also decreased the expression of osteoclast marker genes, including cathepsin K, TRAP, RANK, and NFATc1. Besides, ulinastatin prevented bone loss in ovariectomized C57 mice by inhibiting the formation of osteoclasts. To sum up, this research confirmed that ulinastatin has the ability to inhibit osteoclastogenesis and prevent bone loss, and uPAR plays a crucial role in that process. Therefore, ulinastatin could be chosen as an effective alternative therapeutics for osteoclast-related diseases.